Modulation of the long non-coding RNA Mir155hg by high, but not moderate, hydrostatic pressure in cartilage precursor cells - Kevin Montagne; Katsuko S. Furukawa; Yuki Taninaka; Brandon Ngao; Takashi Ushida (PLoS ONE, 2022)
Osteoarthritis (OA) is the most common joint disease in older adults and is characterized by a gradual degradation of articular cartilage due to decreased cartilage matrix gene expression and increased expression of genes involved in protein degradation, apoptosis and inflammation. Due to the high water content of cartilage, one of the main physical stimuli sensed by chondrocytes is hydrostatic pressure. We previously showed that high pressure above 20 MPa induced gene expression changes in chondrocyte precursor cells similar to what is observed in OA. Micro-RNAs are small non-coding RNAs essential to many physiological and pathological process including OA. As the micro-RNA miR-155 has been found increased in OA chondrocytes, we investigated the effects of high pressure on the expression of the miR-155 host gene Mir155hg. The chondrocyte progenitor cell line ATDC5 was pressurized under hydrostatic pressure up to 25 MPa and the expression of Mir155hg or the resulting micro-RNAs were measured; pharmacological inhibitors were used to identify the signaling pathways involved in the regulation of Mir155hg. We found that Mir155hg is strongly and rapidly up-regulated by high, but not moderate, pressure in chondrocyte progenitor cells. This up-regulation likely involves the membrane channel pannexin-1 and several intracellular signaling molecules including PKC and Src. MiR-155-5p and -3p were also up-regulated by pressure though somewhat later than Mir155hg, and a set of known miR-155-5p target genes, including Ikbke, Smarca4 and Ywhae, was affected by pressure, suggesting that Mir155hg may have important roles in cartilage physiology.